Effects of Traditional Chinese Medicine on Chemotherapy-Induced Myelosuppression and Febrile Neutropenia in Breast Cancer Patients. (12th August 2015) - Tian, Huan; Qin, Wei; Wu, Wenjing; Guo, Pi; Lu, Yong; Liu, Pengxi; Liu, Qiang; Su, Fengxi
Abstract : Title . Chemotherapy-induced myelosuppression lowers the quality of life in breast cancer patients and causes many complications. Traditional Chinese Medicine (TCM) is a widely used complementary and alternative medicine therapies. Objective . To study whether TCM can reduce the incidence of chemotherapy-induced leukopenia, neutropenia, and febrile neutropenia (FN) in breast cancer patients. Methods . The data were analyzed retrospectively between patients who received TCM treatment (group 1, n = 453 ) and patients who did not receive TCM treatment (group 2, n = 359 ). Significant risk factors associated with the occurrence of chemotherapy-induced leukopenia, neutropenia, and FN were identified using multivariate analysis. Propensity score-matched patients were analyzed to adjust for any baseline differences. Results . Group 1 patients had a significantly lower rate of chemotherapy-induced severe leukopenia, neutropenia, and FN, compared with group 2 (43% versus 71%, P < 0.0001, 72% versus 78%, P = 0.005, 6% versus 24%, P < 0.0001, resp.). Multivariate analysis revealed that chemotherapy regimens containing anthracyclines combined with paclitaxel or docetaxel were the most significant predictor. Subgroup analysis indicated that TCM treatment showed benefit in relieving chemotherapy-induced leukopenia and FN in most chemotherapy regimens. Conclusions . TCM treatment could lower the risk of severe chemotherapy-induced leukopenia, neutropenia, and FN in breast cancer patients.